Peran Resepsionis Dalam Memberikan Pelayanan Kepada Tamu Di Hotel X Belitong - Permatasari, Mustika (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
With the development of Belitung, it also affects the competition between hotel managers in attracting tourists to stay at the hotel they manage which is available where the Hotel is a commercial accommodation facility intended as a temporary living facility. The length of time consumers stay at a hotel varies, depending on several things, including consumer interests and hotel attractiveness. Therefore, the good and bad of the hotel depends on the service provided to visitors. The role of the receptionist is necessary for the hotel to serve guests, because for guests the receptionist is the first person to contact during their stay if they need anything. This study aims to determine the role of receptionists in providing services to guests at Hotel X Belitong. In this study the method used is a qualitative method. The result in this study is that there is a standard operating procedure in carrying out services to guests so that guests feel more comfortable when receiving services. In maintaining the service, the receptionist will reconfirm whether the form of service provided is appropriate or there is still something unresolved. The form of communication seen is the Courtesy call attitude carried out after the guest enters the room for approximately 15 minutes to ensure the condition of the room is a problem or not. apply a standard model that guides in serving guests, namely the L.E.A.R.N Model.